Annual reports on NMR spectroscopy. - Webb, G. A. (Graham Alan), 1935- (Annual reports on NMR spectroscopy, 1995)
Over recent years, no other technique has grown to such importance as that of NMR spectroscopy. It is used in all branches of science where precise structural determination is required and where the nature of interactions and reactions in solution is being studied. Annual Reports on NMR Spectroscopy has established itself as a means for the specialist and non-specialist alike to become familiar with new applications of the technique in all branches of chemistry, including biochemistry, and pharmaceutics. This volume focuses on theoretical aspects of NMR nuclear shielding and on applications of NMR to polymer science.